The Influence of Salary, Training and Organizational Culture on Employee Performance in the Jababeka Industrial Area - Hermiati, Novi Fitria; Yustini, Tien (Economic Education Analysis Journal, 2024)
Human resources are the main component for every company to achieve its goals. The strength of human resources is formed by the character or behavior of each employee and the environment within the company. This research aims to find out how salary, training and organizational culture influence employee performance among employees who work in the Jababeka industrial area. This research was conducted on employees who work in the Jababeka industrial area, while the sampling technique used a non-probability sampling method with the Accidental Sampling technique because the number of employees in the Jababeka area is unknown, so the formula needed to determine the sample size is to use the Lemeshow formula . So the minimum sample size required in this research is 97 respondents. In this research, questionnaires were the only data collection technique used. Meanwhile, the statistical test tool used in this research is SmartPLS. From the research that has been carried out, the results obtained show that organizational culture and salary have an influence on employee performance in the Jababeka industrial area and training has no effect on employee performance in the Jababeka industrial area. The results of this research explain that organizational culture has a major role in shaping employee behavior. Meanwhile, salary is a form of company remuneration to employees for their performance. And the last one is training, training has no influence on employee performance.